African trypanosomiasis in Cattle: Working with nature's solution - Murray, M.; Black, Samuel J. (Elsevier, 1985)
Reviews the situation of Trypanosomiasis in cattle in the humid & sub humid areas of Africa. Includes improvement of trypanotolerant breeds; research activities like the control of trypanosome growth, development of effective immune responses & resistance to anaemia.